The 5 A.M. Revolution: Why High Achievers Wake Up Early and How You Can Do It, Too - Dan Luca (New Delhi, India Rupa & Co, 2017)
This book gives the solution to the best life possible: Get up at 5 A.M. and get into the exclusive club of the one percentile in the world. Here's how. First: Get the best sleep possible Learn the fundamentals of a calming and peaceful sleep. Once you solve the sleeping puzzle, you'll be a different person altogether. Second: Have a great morning ritual Practise a world-class morning ritual to kick-start a fantastic day. And by that, it means every single day. Third: Wake up with passion Too many people use sleep as a convenient drug to avoid facing the harsh reality. This book will give you fifty reasons to wake up at 5 A.M. with a smile on your face. Fourth: Implement the right changes in eight weeks In order to massively upgrade your life, more than motivation or discipline, this book will teach you a new structure which will never let you go back to your old ways. Stop feeling so overworked and overwhelmed! Learn the secret to a great life. Buy The 5 A.M. Revolution now to increase your productivity while you gain more balance between your personal and professional life.
Keywords: Psychology Self - Help & Identity -- Psychology Self - Help & Identity; Productivity -- Productivity